Foundational mathematics and reading skills of Filipino students over a generation - Takiko Igarashi; Daniel Suryadarma (Asian Development Bank Institute (ADBI), 2021)
Children around the world largely rely on the formal educational system to teach them foundational mathematics and reading skills. The inability of an educational system to do so may indicate it has structural constraints. In this paper, we take advantage of three rounds of a nationally representative household survey on education and functional literacy implemented by the Philippine Statistics Authority to examine mastery of foundational mathematics and reading skills among students in grades 4-10 students. The three rounds enable us to examine trends in these skills from the turn of the millennium to 2019. We find that a significant proportion of higher-grade students have not yet mastered these foundational skills. We also find that the difference in foundational skills between grade 10 and grade 4 students is small. Based on a comparison between cohorts, we find that foundational mathematics skills continued to decline between the 2003 and 2019 cohorts. Foundational reading skills, however, trended up between 2013 and 2019 after stagnating between 2003 and 2013. The latter is suggestive evidence that major educational reforms implemented by the Philippine government since 2012 may have successfully improved reading skills but not mathematics skills. Overall, the Philippine basic education system, building on its success in increasing access to education for virtually all children, still has ample room to significantly improve its effectiveness.
Keywords: I21; O15; O53; 330; foundational skills; learning outcomes; education quality; Philippines